Menakar Kebebasan Media Massa dan Radikalisme Agama - Mundir (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2016)
Mass media is an abbreviation which comes from mass communication media, is a means of conveying messages and aspirations, as well as a means of communication to disseminate information to the public at large. In the reform era, mass media flourished in various forms, for example TV, radio, internet, newspapers, magazines, tabloids, and so on. The mass media has four functions: an information function (to inform) an education function (to educate), an entertainment function (to entertain), and a social control function (to influence). From a number of mass media, online media (internet) is one of the media that is widely used by the public for various purposes, including the preaching of Islam within moderate and radical boundaries. Well, this paper examines the online mass media (internet), considering that the internet is one of the mass media that is easy to get, cheap in cost, can reach all areas and is not limited by space and time.